Study of Industrial Black Water Treatment Plant Installation Planning System Based on Sewage Treatment Plant - Nandiasa, Jantiara Eka; Nurardiansyah, Ridi (NAROTAMA UNIVERSITY, Indonesia, 2020)
Wastewater in general is water, in general, is a liquid that comes from households, industries, or other public places that usually contain materials or substances that can endanger human life and disturb the environment. Quid comes from households, industries, or other public places that usually contain materials or substances that can endanger human life and disturb the environment. This study to plan, analyze, and assess the performance conditions of wastewater treatment plants (IPAL) at PT XYZ Bekasi Regency on environmental quality standards. Data and information used are data on the amount of wastewater, sources of wastewater, and behavior of water use as well as secondary data in the form of data that the authors surveyed directly at the research location. The processing method of the output value of WWTP uses the research method of the laboratories from the research method in which the output value exceeds the quality standard of LHK Regulation No. 68 the Year 2016 and has exceeded its planning capacity. And what is identified is not safe. An alternative solution to the problem of unsafe output values ??is by planning a new wastewater treatment plant.